Effects Of Oxygen Mass Transfer On Chalcopyrite Leaching By Thiobacillus Ferroxidans - Summary - Othon do Rêgo Monteiro Neto (The Minerals, Metals and Materials Society, 1985)
[The present study has investigated the extraction of copper from a chalcopyrite flotation concentrate using an adapted strain of Thiobacillus ferrooxidans and shake flasks, tank leaching and Warburg respirometer techniques. From the shake flask experiments, the activation energy and the frequency factor have been determined to be ?ka = 59.4 kJ and A = 3.3 x 105 S-1, respectively. The temperature coefficient was found to be Q10 = 2.2 in the range of 20 to 35°C. It was suggested that the reaction mechanism of chalcopyrite leaching by T. ferrooxidans involves the formation of an activated complex. whose thermodynamic values have been calculated to be ?G? = 92.1 kJ, ?S? -148.8 J K-1 and ?H$ = 47.8 kJ. The maximum volumetric oxygen mass transfer coefficient for the reactor leaching was found to be achieved by using an optimum air flow rate of 1970 cm min l at a rotational frequency of 1000 min-1. The highest copper extraction in tank (reactor) leaching experiment was 86.8% after 17 days of leaching, while in the sterile runs the corresponding copper extraction was only 40.1%. The copper extraction was suggested to be diffusion controlled. The power requirement of the aerated reactor was calculated to be Pg = 2.02 watts. During leaching, the oxygen saturation concentration was found to be C* = 6.70 mg dm-3. Using the gassing out method the critical oxygen concentration was assessed to be CCrit 0.05 mg dm 3. From the Warburg experiments, the kinetic parameters of the Monad equation were derived with a new evaluation technique to be Vmsp = 9.0 µm3 02 min-1 mg protein-1 and K = 7.4% pulp density for the effect of substrate concentration. The order of reaction and the overall reaction rate constant were determined from the modified van't Hoff plot to be n = 0.0 and k = 1.49 p dm3 02 min-1 mg Protein -1 for the chalcopyrite concentrate oxidation by T. ferrooxidans. On the basis of this experimental work, a preliminary flow sheet has been proposed for the bioextraction of copper from flotation concentrates.]